TRANSFER OF JAVANESE CULTURE IN THE PRODUCTION OF ENGLISH UTTERANCES AND ITS POSSIBLE IMPACT ON INTER-CULTURAL INTERACTION - FX Nadar (Faculty of Cultural Sciences, Universitas Gadjah Mada, 1999)
This brief paper discusses the ways Javanese speaking English produce utterances in English which show transfer and influence from Javanese culture . It argues that cultural transfer from first language has possible negative impact in intercultural interaction . First, some important characteristics of Javanese culture will be discussed, then examples of utterances commonly produced by Javanese speaking English will be given . The writer collected the data from his classroom activities, his personal experience and also from limited studies on the ways Javanese speaking English produce certain acts by using questionnaires . Finally this paper argues that as cultural transfer may influence the smoothness of interaction between Javanese speaking English with speakers English of other cultures and particularly with native speakers of English, it is essential that teachers as well as learners of English in Indonesia should be aware of such cultural transfer and include the discussion of cultural differences in their teaming process.